Ensuring Satellite Operational Integrity: A Power Budget Analysis for Next Generation Satellites - Atif Mahmood; Ayman Muhammad Abdallah; Bazilah Binti Baharom; Asia Saeed Kajo Habilah (IEEE Access)
As satellite missions become more complex, reliable power management is crucial for success. Traditional power budgeting approaches often operate at the system level, leading to inefficiencies in power allocation, particularly during critical phases such as eclipse mode. This study presents a component-level power budgeting framework to enhance operational integrity for next-generation satellites, specifically focusing on power load calculation, power generation, and battery capacity requirements. Key challenges such as power shortages, thermal fluctuations, and battery management require efficient power allocation and thermal control to ensure system reliability. Additionally, laser communication, while a critical capability for advanced satellites, becomes more complex during eclipse mode as in this period the mission execution will totally depends on the onboard available power. This analysis is based on detailed component-level power load calculations for eclipse mode. The total power load in this scenario is 38.922 W, with an operational mode of 27.5179 W, accounting for the power consumption of other subsystems. These calculations incorporate each module’s power load, weighted by its duty cycle per orbit. The solar panels generate 65 W of power, with an effective power output of 45.599 W, as simulated in STK software. The eclipse mode, at an altitude of 525 km and an inclination angle of 83 degrees, lasts for 37.7% of the orbit, resulting in a power consumption of 27.343 W during this time. The calculated power consumption in eclipse mode is 27.343 W, with a minor error of 0.175 W. To meet battery requirements, the battery must provide at least 48.34 W, considering an 80% Depth of Discharge (DOD), for a 10-second high-power communication window. The battery capacity should exceed 48.34 W to ensure safe operation in eclipse mode. Based on these calculations, the satellite’s power generation and storage system are sufficient to support its operations during eclipse mode, ensuring reliable and uninterrupted performance.